Cervical cytology: are national guidelines adequate for women attending genitourinary medicine clinics?. Issue 5 (1st October 1999) - Foley, E; Harindra, V
Abstract : OBJECTIVES: To study whether all women attending a genitourinary medicine (GUM) clinic warrant a cervical smear as part of a routine screen for infection, or whether this "at risk" population is adequately covered by the national screening programme. METHODS: A cervical smear and a screen for sexually transmitted infections (STI) were taken from 900 women attending a GUM clinic between May 1996 and April 1997. RESULTS: Of 812 smears available for analysis, 613 (75.5%) were normal, 176 (21.7%) were mildly abnormal, and 23 (2.8%) were moderately or severely abnormal. In the absence of an STI there was a 14% (37/273) risk of having an abnormal cervical smear. In the presence of cervicitis the risk was 26% (22/84) and with genital warts the risk was 34% (75/215). CONCLUSION: The national screening programme guidelines for cervical cytology should be followed in the GUM clinic. There is no benefit in performing extra smears outside the programme nor in adopting a policy of universal screening.